Aluminum Chloride Mediated Reactions of N-Alkylated Tosylhydrazones and Terminal Alkynes: A Regioselective Approach to 1,3,5-Trisubstituted Pyrazoles - Tang, Meng; Wang, Yun; Wang, Hu; Kong, Yuanfang (Synthesis, 2016)
Aluminum chloride mediated reactions of N-alkylated tosylhydrazones and terminal alkynes are reported. The protocol is applied to a wide range of substrates, and demonstrates excellent functional group tolerance. A series of 1,3,5-trisubstituted pyrazoles is prepared in good to high yields with complete regioselectivity.
Keywords: aluminum chloride; tosylhydrazones; alkynes; pyrazoles; regioselectivity